2022
DOI: 10.2147/jpr.s349251
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Causal Relationships Between Low Back Pain Complications, Metabolic Factors, and Comorbidities

Abstract: Purpose Low back pain (LBP) is one of the major disabling health conditions in aging societies presenting significant cost burdens to health and social care systems. Its complications and associated disability are often accompanied by mental disorders, metabolic comorbidities, changed body composition, and inflammation. However, their mutual relationships in LBP-associated disability remain unclear. Methods In the present case-control study, a self-report validated ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 91 publications
2
19
0
1
Order By: Relevance
“…Blood samples were used to assay plasma concentrations of biochemical factors relevant to this study. Further details have been reported in our recent studies on this subject [ 3 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Blood samples were used to assay plasma concentrations of biochemical factors relevant to this study. Further details have been reported in our recent studies on this subject [ 3 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, the pathogenesis of this multifactorial condition is still not fully understood. We recently reported that complex, age-associated and most probably, hierarchical relationships exist between LBP disability, inflammation-related soluble markers, body composition parameters, and the sideways curve of the spine – scoliosis [ 3 , 4 ]. However, it is unclear whether these factors affect LBP via spine-morphological changes, such as spinal osteoarthritis, specifically, facet joint osteoarthritis (FJOA) and lumbar disc degeneration (LDD), acknowledged as the major contributors to LBP [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…La discapacidad tiene un impacto negativo y una influencia importante en la calidad de vida física en individuos con dolor lumbar crónico. Se ha evidenciado en diferentes estudios que la discapacidad lumbar se asocia de manera significativa a factores bioquímicos y parámetros de composición corporal y se agrava por trastornos mentales y comorbilidades metabólicas (4) .…”
Section: Introductionunclassified